2012
DOI: 10.1136/bcr-2012-006392
|View full text |Cite
|
Sign up to set email alerts
|

Multiple sclerosis-like neurological manifestations in a coeliac patient: nothing is as it seems

Abstract: Cobalamin (vitamin B₁₂) deficiency occurs with several disorders, involving different organs and systems, including blood, bowel, nervous system and eyes. Although the most important features are usually haematological ones, presence of neurological involvement, in the absence of blood count alterations, has just been described in the literature. Here we report the case of a 48-year-old man, suffering from coeliac disease for approximately 5 years, vegetarian, who was admitted to our department, referring dysa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
1
0
1
Order By: Relevance
“…Ciecierega et al 5 documented a rare co-existence of Hartnup disease in the setting of CD secondary to combined deficiencies in amino acids and proteins. Mansueto et al 6 reported a case of severe vitamin b12 deficiency resulting in multiple sclerosis like presentation secondary to underlying CD. A similar case of myelopathy was reported by Cavallieri et al 7 when severe copper deficiency resulted in a subacute combined degeneration presentation.…”
Section: Discussionmentioning
confidence: 99%
“…Ciecierega et al 5 documented a rare co-existence of Hartnup disease in the setting of CD secondary to combined deficiencies in amino acids and proteins. Mansueto et al 6 reported a case of severe vitamin b12 deficiency resulting in multiple sclerosis like presentation secondary to underlying CD. A similar case of myelopathy was reported by Cavallieri et al 7 when severe copper deficiency resulted in a subacute combined degeneration presentation.…”
Section: Discussionmentioning
confidence: 99%
“…К неифекционным болезням, имеющим сходные с РС клинико-инструментальные признаки, следует отнести антифосфолипидный синдром [55], нейроформу синдрома Шегрена [110], оптическую невропатию Лебера [70,117] (рис. 5), параинфекционные неврологические поражения [118], целиакию [73], полигландулярный аутоиммунный синдром [37], адренолейкодистрофию у Рис. 4.…”
Section: инфекционные агентыunclassified